Ingeborg Gabriel, Peter G. Kirchschläger and Richard Sturn, eds. "Eine Wirtschaft, die Leben fördert, Wirtschafts- und unternehmensethische Reflexionen im Anschluss an Papst Franziskus" ["An economy that supports life. Economical and business ethics reflections following Pope Francis"]. Ostfildern: Matthias Grünewald Verlag, 2017. 353 p. - MARKSTEINER-UNGUREANU, Cezar (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2018)
This collected volume deals with the major ecologic-social crises caused principally by the current configuration of the global economic system. The title of this book represents a programmatic answer to the often-cited words of Pope Francis from Evangelii Gaudium (shortened as: EG) Such an economy kills (EG 53). This assertion of the Pope refers primarily to an economy of exclusion, inequality, and financial speculation that only focuses on its material dimension (idolatry). The present volume gathers papers of distinguished scholars both in German and English. It attempts to analyze the contemporary socio-ecological crisis from different perspectives such as (Christian) social ethics, economics, and political science. Consequently, the book explores several alternative solutions based primarily on the social ethical doctrine of the Catholic Church on the current socio-ecological crises. The papers address topics such as fundamental questions of economic ethics (Gabriel Ingeborg), social justice (Georges Enderle, Richard Sturn), social market economy (Markus Vogt and Gerhard Kruip), financial economics and ethics (Bernhard Emunds and Wilfried Stadler), ecological challenges (Stefano Zamagni and Franz Gassner), and business ethics (Michael Pirson).